# math

posted by .

Solve for x: log3(x^2-4)-log3(x+2)=2

• math -

log3(x^2-4)-log3(x+2)=2
log3 [(x^2-4)/x+2)] = 2
log3 [(x+2)(x-2)/(x+2)] = 2
log3 (x-2) = 2
x-2 = 3^2
x = 11

• math -

log3 (x^2-4) -log3 (x+2)=2
log3 [(x^2-4)/x+2)] = 2
log3 [(x+2)(x-2)/(x+2)] = 2
log3 (x-2) = 2
x-2 = 3^2
x = 11

Adam, why would you just cut-and-paste my solution and claim it as yours ?

You didn't even bother to fix my error in the 2nd line, where I missed a bracket.

## Similar Questions

1. ### Math

(I have two questions) 1. Solve for x without a calculator: log3(x^2)=2log3(4)-4log3(5) This is what I have so far: 2log3(x)=log3(4^2)-log3(5^4) 2log3(x)=log3(16/625) ...and now I'm stuck. 2. Simplify: 2log4(9)-2log3 <--how do you …
2. ### Precalculus

Please help me with these questions ASAP!! Suppose that f(x)=log3(x-1) a)If f(6)=1.4 and f(8)=1.7,then evaluate log3(35) and log3(7/5). b)If f(3)=0.6, find log9(2).
3. ### Algebra 1

Lesson 3 Assignment .Explain the differences between solving these two equations: By steps log3(x - 1) = 4 AND log3(x - 1) = log3^4
4. ### ALGEBRA 1

Lesson 3 Assignment .Explain the differences between solving these two equations: By steps log3(x - 1) = 4 AND log3(x - 1) = log3^4
5. ### Math

Solve the logarithmic equation. Express your solutions in exact form only. Please show all of your work. log3(x+2) + log3(x+8) – 2 = log3(x+3)
6. ### math

Solve for x in the following equations. (4 marks) log3(x - 5) + log3(x + 3) = 2 <--- both log3.. 3 is subscript log7x + log7(x - 1) = log72x <--- all log7.. 7 is subscript.
7. ### Math

Express the following as a logarithm and simplify. 1. log(3x^2 + 11x - 20) - log(3x - 4) 2. 1/6 log3 27 + log3 18 - log3 2 3. log5 cube root of 625 4. 2loga x^3 + 3loga y + 4loga z - 3logz w
8. ### Math

Express the following as a logarithm and simplify. 1. log(3x^2 + 11x - 20) - log(3x - 4) 2. 1/6 log3 27 + log3 18 - log3 2 3. log5 cube root of 625 4. 2loga x^3 + 3loga y + 4loga z - 3logz w
9. ### Pre-calculus

Hi i need to find x in 9^(2x-6)=6^(8x-5) So what i did was: 3^(4x-12)=6^(8x-5) log3(3)^(4x-12)=log3(6)^(8x-5) 4x-12=(8x-5)log3(6) now i'm stuck. and i actually feel that the whole thing is wrong. help, pls
10. ### Math

Given that x=log3^5 and y=log3^2, rewrite log3^60 in terms of x and y.

More Similar Questions